The Role of Investment in the Production Equipment Modernization and Its Effect on Productivity - VOYTSEKHOVSKA, Yuliya; BUBLYK, Lilia; KUKHARUK, Anna; PURHANI, Safar Hasan; BILOVA, Natalia (Theoretical and Practical Research in Economic Fields, 2024)
Purpose: The aim of the study is to determine the role of investment in the production equipment modernization and to assess the impact of this investment on the company’s productivity. Methodology: The research employed calculation of the Weighted Average Cost of Capital (WACC), as well as the Net Present Value (NPV), Profitability Index (PI) as the methods. The final stage was the application of the correlation coefficient. For the company Builders FirstSource Inc used as an example the calculated WACC was 8.74%, for Hardie Industries plc. this figure was 9.31, for Boral — 4.3%, and for Grafton plc — 5.6%. The Profitability Index was 1.30 (Builders FirstSource Inc,), 2.34 (Hardie Industries plc), 1.51 and 1.46 for Boral and Grafton plc. The Net Present Value (NPV) amounted to $10,863 million and $128,173 million for Builders FirstSource Inc and Hardie Industries plc., respectively. Findings: The study showed a close relationship between productivity and investment in equipment modernization, as the correlation coefficients are 0.991 (Builders FirstSource Inc,), 0.994 (Hardie Industries plc), 0.83 (Boral), and 0.97 (Grafton plc), indicating a close correlation. The obtained results can be successfully used by manufacturing companies to assess the feasibility of investment in modernization. Originality: A possible direction of further research is the introduction of gradation of investments in modernization, with clarification of the types of modernization and the type of equipment that will be modernized.